2019
DOI: 10.1038/s41598-019-48504-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the photovoltaic performance of hybrid heterojunction solar cells by passivation of silicon surface via a simple 1-min annealing process

Abstract: Solution-based heterojunction technology is emerging for facile fabrication of silicon (Si)-based solar cells. Surface passivation of Si substrate has been well established to improve the photovoltaic (PV) performance for the conventional bulk Si cells. However, the impact is still not seen for the heterojunction cells. Here, we developed a facile and repeatable method to passivate the Si surface by a simple 1-min annealing process in vacuum, and integrated it into the heterojunction cells with poly(3,4-ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We define the short-circuit current J sc as the current measured when a zero bias is applied across the junction, and the open circuit voltage V oc as the voltage across the device when no electrical current is measured. While V oc ( ∼ 0.5 V) is comparable to that observed earlier in cuprate based photovoltaic cells 48,49 , J sc is several orders of magnitude higher 48,49 and indeed compares to that of silicon based devices 50 . Figure 4b displays V oc as a function of the junction's remnant conductance measured at V read = 100 mV, G 100 .…”
Section: Optical Effectssupporting
confidence: 82%
“…We define the short-circuit current J sc as the current measured when a zero bias is applied across the junction, and the open circuit voltage V oc as the voltage across the device when no electrical current is measured. While V oc ( ∼ 0.5 V) is comparable to that observed earlier in cuprate based photovoltaic cells 48,49 , J sc is several orders of magnitude higher 48,49 and indeed compares to that of silicon based devices 50 . Figure 4b displays V oc as a function of the junction's remnant conductance measured at V read = 100 mV, G 100 .…”
Section: Optical Effectssupporting
confidence: 82%
“…Among the organic materials, poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a widely used polymer in optoelectronic devices such as photo‐detectors, light emitting diodes, and photovoltaics . Its numerous advantages include good environmental stability, low band gap, high optical transparency, low redox potential, high work function, water solubility, hole conducting ability, ease of deposition by solution process, and p‐type semiconductor characteristics . Though the superior characteristics of PEDOT:PSS ensures its role as a promising material for replacing inorganic semiconductors in plastic electronics application, PEDOT:PSS thin films possess a drawback due to their lower conductivity compared to indium–tin oxide (ITO) and other conductive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Jin et al reported that a floating method of a similarly filtrated SWNT thin film apart from MCE, and the as-floated SWNT film was picked up on a substrate (Method B). [17] See-through perovskite (PVK) solar cells have been successfully prepared using top-contact SWNT thin films [18,19] by a dry filter-transfer method using MCE membranes reported by Kauppinen et al [20] Simply structured crystalline Si-SWNT heterojunction solar cells have been prepared by the solution-processed [21][22][23][24][25][26][27][28] and dry filter-transfer [29][30][31][32] methods with increasing photo-conversion efficiencies up to ≥17%. [25,31,33,34] See-through solar cells are indispensable for state-of-the-art tandem devices combined with crystalline Si solar cells driven by visible and near IR lights.…”
mentioning
confidence: 99%